The Influence Of The Human Development Index And The Rate Of Open Unemployment On The Number Of Poor Population In Lamongan District - Ririn Aprilia Dewanti; Sishadiyati Sishadiyati (Cita konsultindo, 2024)
Sustainable Development Goals (SDGs) or Sustainable Development is a global and national commitment to improve people's welfare, which includes 17 goals until 2030. The main goal emphasized by the SDGs is